Determinación de urea y creatinina como indicador de nefropatía en pacientes diabéticos del IESS. periodo enero-junio del 2013. - Álvarez Armijos, Marjorie Rosana (2013)
DETERMINE OF UREA AND CREATININA AS INDICATOR NEPHROPATHY IN DIABETIC PATIENTS DEL IESS. PERIOD JANUARY – JUNE 2013. The present study was carried out with the purpose of to determine urea and creatinina by means of the method colorimetric in diabetic patients and to relate the results according to the time of evolution of the illness, study that was of descriptive type and of traverse court with a sample of 90 people with diagnostic of diabetes mellitus that completed with the inclusion approaches and exclusion. Reaching the following conclusions was found that the values of the tests Urea 19%, creatinina 81% was increased, in those people that suffer diabetes for a bigger period to 5 years the urea this increased in 14, 5% and the creatinina this increased in 58, 9% in people that suffer diabetes for more than 5 years and in 17, 5% in people that suffer the illness among 3 to 5 years. Keywords: diabetes mellitus, serum urea and creatinina, diabetic nephropathy, progression of the disease.